(untitled) (Research, Society and Development, 2023)
In Brazil, they are recommended as Integrative and Complementary Health Practices (PICS) in the SUS, which are transversal and multidisciplinary therapeutic practices, outside of disease prevention and health recovery, through comprehensive patient care. One example is ozone therapy, which uses medicinal ozone to treat various pathologies. The present study aims to investigate scientific evidence available in the literature, which proves the safety of ozone therapy as an integrative and complementary practice of the SUS. A narrative literature review was carried out, considering articles published between 2018 and 2023, in Portuguese and English, available in full and free of charge and which addressed the topic. It was found that ozone therapy is a promising integrative and complementary practice, as it presents medicinal properties such as antioxidant, analgesic, regenerative, blood circulation stimulating, healing, bactericidal and fungicidal, antiviral effects, among others, being an important therapeutic innovation to be effective. Updated in the SUS, to provide a wider arsenal of effective treatments to users. However, there is still a lack of information about this therapy, which highlights the need for new studies, which provide greater support for its use in the Brazilian Unified Health System.